2018
DOI: 10.1017/s0033291718000302
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the management of cardiovascular risk factors in patients with psychiatric disorders: a systematic review and meta-analysis

Abstract: A proactive clinical management, together with further studies, are needed to reduce the CV morbidity and mortality of patients with psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 71 publications
(173 reference statements)
0
27
0
3
Order By: Relevance
“…by attending follow-up appointments). 124,126 Other factors explaining why physicians may be reluctant to offer some medical procedures because of the ensuing psychological stress, along with concerns about capacity, informed consent or compliance with postoperative care, or the presence of contra-indications such as substance abuse and smoking. 126 However, contra-indications to specialized interventions, such as smoking or problems with informed consent, are less relevant to the prescription of vascular drugs such as ACE inhibitors, beta-blockers, or statins known to reduce subsequent morbidity and mortality.…”
Section: Looking Beyond Lifestyle: Health Provider and System-level Fmentioning
confidence: 99%
See 2 more Smart Citations
“…by attending follow-up appointments). 124,126 Other factors explaining why physicians may be reluctant to offer some medical procedures because of the ensuing psychological stress, along with concerns about capacity, informed consent or compliance with postoperative care, or the presence of contra-indications such as substance abuse and smoking. 126 However, contra-indications to specialized interventions, such as smoking or problems with informed consent, are less relevant to the prescription of vascular drugs such as ACE inhibitors, beta-blockers, or statins known to reduce subsequent morbidity and mortality.…”
Section: Looking Beyond Lifestyle: Health Provider and System-level Fmentioning
confidence: 99%
“…124,126 Other factors explaining why physicians may be reluctant to offer some medical procedures because of the ensuing psychological stress, along with concerns about capacity, informed consent or compliance with postoperative care, or the presence of contra-indications such as substance abuse and smoking. 126 However, contra-indications to specialized interventions, such as smoking or problems with informed consent, are less relevant to the prescription of vascular drugs such as ACE inhibitors, beta-blockers, or statins known to reduce subsequent morbidity and mortality. 127 Furthermore, recent data have shown that people with schizophrenia are equally adherent to diabetes medication as the general population, thus further supporting the need for healthcare providers to remain optimistic about prescribing cardiometabolic medications in people with mental illness.…”
Section: Looking Beyond Lifestyle: Health Provider and System-level Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, less experienced providers may be uncomfortable with serious mental illness and may avoid intensifying their interaction with a patient by asking probing questions about physical symptoms and performing a physical exam (41). Indeed, there is ample evidence that individuals with schizophrenia are less likely than their peers without any psychiatric illnesses to receive medical procedures and treatments for a range of conditions including cancer screening and treatment (45), use of antihypertensive and lipidlowering drugs (46) and appropriate diabetes care (including A1C and cholesterol testing, eye and feet exams, etc.) (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…People with psychosis have increased risk of cardiovascular illness (Foguet-Boreu et al 2016) including in early phases of the illness (Correll et al 2014). But they are less likely than others to receive appropriate health care (Ayerbe et al 2018;De Hert et al 2011;Laursen et al 2014;Mitchell et al 2015). Mental health care and primary care must collaborate to improve monitoring and physical health care for people with psychosis (De Hert et al 2009).…”
Section: Monitoring Cardiovascular Risk Factors and Treatment Of Physmentioning
confidence: 99%